Damping studies on fibre-reinforced epoxy polymer concrete using Taguchi design of experiments. (2015) - Bedi, Raman; Sharma, Renu
In the present study, the damping characteristics of glass fibre-reinforced epoxy polymer concrete is evaluated and compared with that of cast iron. Effect of resin content, fibre content, filler content and aggregate mix type on damping of polymer concrete has been studied using Taguchi design of experiments methodology. Fly ash is used as filler and the foundry sand with different size combinations is used as aggregate. Nine different polymer concrete mix proportions based on Taguchi L9 array were tested for damping ratio. The samples were prepared and tested through vibration analyser, which is used for modal analysis. It has been concluded that the fibre reinforced polymer concrete has damping ratios two to three times higher than the cast iron. The aggregate mix proportion is the most important factor affecting damping of fibre reinforced epoxy polymer concrete. Further, an optimised combination is obtained that gives maximum damping ratio.